Secondary School Teachers ’ Experiences of Using Action Research in Classroom Practices - Mwakabenga, Rehema Japhet (Papers in Education and Development, 2022)
This qualitative study reports part of an intervention study that investigated how four secondary school teachers enhanced their ability to participate in a teacher-led professional learning through action research. Specifically, this paper focuses on the secondary school teachers ' knowledge and ability of engaging in action research to improve their pedagogical practices. The most important finding indicated that in the course of intervention, the teachers learned to carry out systematic action research as a form of professional learning that impacted their classroom practices. While the findings from this study cannot be generalized to other teachers and school contexts, the experiences of the four teachers provide some insights to other teachers and educational leaders on the use of action research. Keywords: Classroom practices, collaborative action research, teachers ' inquiry cycle, student learning